2020
DOI: 10.1177/016146812012200505
|View full text |Cite
|
Sign up to set email alerts
|

Does Neighborhood Gentrification Create School Desegregation?

Abstract: Background/Context Race and class inequality have long governed patterns of residential and school segregation across America. However, as neighborhoods across the country that have historically been home to residents of color experience an influx of White and middle-class residents, new questions arise as to whether these demographic shifts in neighborhoods correspond to school-level demographic changes. Purpose: This study examines Washington, DC's, most gentrifying areas, and the impact on racial diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
(63 reference statements)
2
9
0
Order By: Relevance
“…Our findings are consistent with recent research concerning neighborhood changes and schools showing that at least on a small, localized scale, largely White and middle-to upper-class families are beginning to engage with urban school districts (Diem et al, 2019;Mordechay & Ayscue, 2020;Stillman, 2012). In addition, our findings are similar to those recently reported by Cordova-Cobo and Ellen (2019), who analyzed the links between neighborhood and school diversity in across NYC.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with recent research concerning neighborhood changes and schools showing that at least on a small, localized scale, largely White and middle-to upper-class families are beginning to engage with urban school districts (Diem et al, 2019;Mordechay & Ayscue, 2020;Stillman, 2012). In addition, our findings are similar to those recently reported by Cordova-Cobo and Ellen (2019), who analyzed the links between neighborhood and school diversity in across NYC.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in elementary enrollment of White students in gentrifying areas aligns with previous studies that have found middle-class and White families increasingly choosing neighborhood public schools (Friedus, 2019; Mordechay & Ayscue, 2020; Stillman, 2012). Prior research has also suggested that gentrifying families tend to cluster their children into a few “vetted” schools, indicating they are not comfortable sending their children to a neighborhood public school unless other gentrifier families are also attending (Jordan & Gallagher, 2015; Kimelberg & Billingham, 2012).…”
Section: Resultssupporting
confidence: 87%
“…White flight strategies and colonisation strategies may coexist in gentrified neighbourhoods and produce different patterns of mobility and different effects on school segregation (Candipan, 2019(Candipan, , 2020Mordechay & Ayscue, 2020;Pearman, 2019).…”
Section: Socio-spatial Inequalities and School Choicementioning
confidence: 99%
“…Parents enrol their children in very different types of schools even if they live in the same neighbourhood in a process of ‘disaffiliation and selective belonging’ (Boterman, 2020, p. 1). White flight strategies and colonisation strategies may coexist in gentrified neighbourhoods and produce different patterns of mobility and different effects on school segregation (Candipan, 2019, 2020; Mordechay & Ayscue, 2020; Pearman, 2019).…”
Section: Socio‐spatial Inequalities and School Choicementioning
confidence: 99%
“…As the racial and socioeconomic composition of a neighborhood change, the enrollment of the neighborhood school may also change, reflecting the shifting demographics of the local community (Green et al, 2020; Mordechay & Ayscue, 2020; Posey-Maddox, 2014). While gentrification may create an opportunity for creating a more diverse, integrated school, tensions arise that must be addressed through a focus on leadership, equity, and intercultural awareness (Mordechay, 2022; Siegel-Hawley et al, 2017).…”
mentioning
confidence: 99%